2017
DOI: 10.3389/fphar.2017.00181
|View full text |Cite
|
Sign up to set email alerts
|

Identification of NF-κB as Determinant of Posttraumatic Stress Disorder and Its Inhibition by the Chinese Herbal Remedy Free and Easy Wanderer

Abstract: Posttraumatic stress disorder (PTSD) is a mental disorder developing after exposure to traumatic events. Although psychotherapy reveals some therapeutic effectiveness, clinically sustainable cure is still uncertain. Some Chinese herbal formulae are reported to work well clinically against mental diseases in Asian countries, but the safety and their mode of action are still unclear. In this study, we investigated the mechanisms of Chinese remedy free and easy wanderer (FAEW) on PTSD. We used a reverse pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…It is reported that these compositions could inhibit the phosphorylation of IκB and block NF-κB transcription factor p50/p65 activation [51]. In addition, paeoniflorin could affect DNA binding ability of nuclear translocation p65 [51,52]. Thus, we speculated that SGD affects NF-κB activation by inhibiting IκB phosphorylation and blocks DNA binding ability of NF-κB transcription factor p50/p65.…”
Section: Discussionmentioning
confidence: 97%
“…It is reported that these compositions could inhibit the phosphorylation of IκB and block NF-κB transcription factor p50/p65 activation [51]. In addition, paeoniflorin could affect DNA binding ability of nuclear translocation p65 [51,52]. Thus, we speculated that SGD affects NF-κB activation by inhibiting IκB phosphorylation and blocks DNA binding ability of NF-κB transcription factor p50/p65.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that liquiritin, isoliquiritin and isoliquirigenin have anticancer effects, individually and in a combination of the three of them (Zhou and Ho, 2014). Isoliquiritin has anti-allergic, anti-depressive, antifungal and anti-inflammatory effects (Hong et al., 2017). Liquiritin has anti-cerebral ischemic, anti-depressive, anti-endothelial dysfunction, anti-melasma, anti-myocardial fibrotic, anti-Parkinsonian, bronchial-protective, cognition enhancing and neuroprotective effects (Hong et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Isoliquiritin has anti-allergic, anti-depressive, antifungal and anti-inflammatory effects (Hong et al., 2017). Liquiritin has anti-cerebral ischemic, anti-depressive, anti-endothelial dysfunction, anti-melasma, anti-myocardial fibrotic, anti-Parkinsonian, bronchial-protective, cognition enhancing and neuroprotective effects (Hong et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…PDB files of proteins were downloaded from the RCSB Protein Data Bank 2 . Molecular docking was carried out with Auto-Dock Vina (The Scripps Research Institute, La Jolla, CA, United States) following a previously reported protocol ( Hong et al, 2017 ). Discovery Studio 4.5 (BIOVIA, Beijing, China) was used for the visualization of the binding modes obtained from the docking.…”
Section: Methodsmentioning
confidence: 99%